Study on the inflow of biogenic substances into lakes - Litvinaitis, Andrius; Bagdžiūnaitė-Litvinaitienė, Lina (International Conference “Environmental Engineering”, 2023)
Changes in the ecosystems of lakes and their shores caused by anthropogenic impact have a huge influence on the quality of the landscape. The article analyzes the inflow of biogenic substances into lakes Lūkstas and Paršežeris. The spread of Quaternary sediments of lake basins, land use distribution, ongoing economic activities, activity planning and the effectiveness of water conservation measures in the dry year of 2020 was analyzed to study in detail. The planned and actual amounts of biogenic substances entering the lakes through seven surface water tributaries were evaluated. It has been established that the environmental protection measures implemented in the Lūkstas and Paršežeris lakes basins over the last decade are effective. Calculations and analysis of the loads of biogenic materials in the investigated lake tributary basins based on the results of natural studies showed that the values of biogenic material loads do not exceed the values modeled in the modeling done in the work and in the river basin management plans.
Keywords: biogens; lake pollution; anthropogenic activity; diffuse pollution; ecological condition